Quantitative Analysis of Factors Influencing the Price of Gold - Mo, Kwan Mo (2011)
Gold is widely used throughout the world nowadays. It is mainly for monetary exchange, store of value purpose, a safe-haven tool when kinds of uncertainties increase and it is also a kind of speculative investment. The gold price was around US$300 per ounce in the 1970s and skyrocketed to above US$1,400 in March 2011 but the price fluctuated a lot within this period. As a result of the Quantitative Easing (QE) measures implemented by the advanced economies and the events happening around the world, the world is now facing with the escalating price of commodities, such as gold and oil etc.